I FLOW GENNEM BYEN - FÆNOMENET “PARKOUR” I DET SENMODERNE BYRUM - Klausen, Maja (K&K - Kultur og Klasse, 2010)
FLOWING THROUGH THE CITY This article discusses the phenomenon of “parkour” and characterises it as a global, urban subculture closely connected to the space of the city and to the use of the digital camera, a mobile technology. The article starts out by framing parkour firstly through its relation to the Situationist International, more specifically the psycho-cartographic technique of the “dérive” and the “détournement”; and secondly through a comparison with the flâneur, which like the Situationist International is a concept tied to modernity. However, it is pointed out that parkour differs from its modern predecessors in its subversive qualities and recontextualising potential, which alternates the way we think of and use the city. Parkour is also analysed through neovitalistic theories represented by Deleuze and Guattari, and Amin and Thrift’s “new urbanism” paradigm. Referring to the concept of new urbanism, the article starts by indicating that parkour and the city co-evolve with one another through the concept of “flow”. For the practitioner of parkour (the “traceur”), flow means moving smoothly through the city, and in doing so the traceur incorporates the movements and fluxes of the city. Drawing on Deleuze and Guattari and Scott Lash, parkour is described as puissance – defined as “a will to” – which creates a Deleuzean “smooth space” in the “striated space” of the city. Thus parkour is seen as the creative, critical and subversive use of spaces in the city which otherwise could be said to lack experiential potential.